How does dose impact on the severity of food‐induced allergic reactions, and can this improve risk assessment for allergenic foods?: Report from an ILSI Europe Food Allergy Task Force Expert Group and Workshop. Issue 7 (9th February 2018) - Dubois, A. E. J.; Turner, P. J.; Hourihane, J.; Ballmer‐Weber, B.; Beyer, K.; Chan, C.‐H.; Gowland, M. H.; O'Hagan, S.; Regent, L.; Remington, B.; Schnadt, S.; Stroheker, T.; et al.
Abstract: Quantitative risk assessment (QRA) for food allergens has made considerable progress in recent years, yet acceptability of its outcomes remains stymied because of the limited extent to which it has been possible to incorporate severity as a variable. Reaction severity, particularly following accidental exposure, depends on multiple factors, related to the allergen, the host and any treatments, which might be administered. Some of these factors are plausibly still unknown. Quantitative risk assessment shows that limiting exposure through control of dose reduces the rates of reactions in allergic populations, but its impact on the relative frequency of severe reactions at different doses is unclear. Food challenge studies suggest that the relationship between dose of allergenic food and reaction severity is complex even under relatively controlled conditions. Because of these complexities, epidemiological studies provide very limited insight into this aspect of the dose‐response relationship. Emerging data from single‐dose challenges suggest that graded food challenges may overestimate the rate of severe reactions. It may be necessary to generate new data (such as those from single‐dose challenges) to reliably identify the effect of dose on severity for use in QRA. Success will reduce uncertainty in the susceptible population and improve consumer choice.